Inkjet‐Printed Metal–Organic Frameworks for Smart E‐Textile Supercapacitors - M. R. Islam; S. Afroj; S. Tan; S. J. Eichhorn; K. S. Novoselov; N. Karim (EcoMat)
ABSTRACT Wearable electronic textiles (e‐textiles) present a transformative platform for integrating real‐time health monitoring devices into everyday garments. Despite their promise, the development of flexible, efficient, and reliable on‐body energy storage remains a major bottleneck. Inkjet printing, known for its precision and compatibility with various substrates, emerges as a viable method for fabricating energy devices on textiles. Metal–organic frameworks (MOFs) have shown great promise in prior studies for enabling flexible and high‐performance energy storage in wearable electronics. Here, we present a novel strategy for engineering metal–organic framework (MOF)‐based e‐textiles as electrodes for a solid‐state textile supercapacitor, utilizing inkjet printing technology. For the first time, standalone MOF inks were successfully deposited on textile substrates, producing highly flexible and washable conductive fabrics. These MOF‐integrated textiles functioned as supercapacitor electrodes, achieving outstanding electrochemical performance with areal and gravimetric capacitances reaching ~354 mF cm−2 and ~87 F g−1, at a 1 mV s−1 scan rate respectively. The devices also demonstrated a high energy density of approximately 196 μW h cm−2 with a remarkable power density of ~54 385 μW cm−2, with nearly 99% retention after 1000 charge–discharge cycles. These results establish MOF‐based e‐textiles as a promising avenue for the next‐generation of wearable energy storage systems.